Gestures and Their Meaning of Main Character in Alex Hardcastleâ€™s Movie â€œSenior Year (2022)â€ - Wilda Wardani Sitorus; Rita Hartati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
This study analyzes gestures and their meaning in Senior Year (2022) movie. The objectives of this study are (1) to find out the types and their meaning used by the main character, and (2) to analyze the meanings of gestures in relation to the semantic meaning of the main character. This study used a qualitative descriptive method using the theory of types and meaning of gestures by David McNeil and Levy (2005), and Semantic Meaning by Chaer (1994). This study showed that 86 data had been found. There are 12 (14%) data as iconic gestures, 13 (15%) data as deictic gestures, 16 (19%) data as metaphor gestures, and 45 (52%) data as beat gestures. The meaning of the gesture used by the main character also varies based on gesture. The meaning of gesture is supported by the utterances in the dialogue (Semantic Meaning). It means that the use of gestures related to the meaning of utterances. But, there are some data that do not have a cultural meaning and no relation to the semantic meaning, such as beat type. A beat gesture is a simple gesture a rhythmic movement that does not express semantic content. The main character used beat gestures to lose nervousness, to get more relaxed, to be more effective and expressive, and to increase self-confidence.Keywords: Gesture, Meaning Gesture, Semantic Meaning, Movie.